1991
DOI: 10.1080/0267257x.1991.9964155
|View full text |Cite
|
Sign up to set email alerts
|

Industrial mail surveys: The costs and benefits of telephone pre‐notification

Abstract: Industrial Mail Surveys: The Costs and Benefits of Telephone Pre-notificationOver the past 5 years a trend towards increased usage of mail surveys has been identified and the reasons for this as well as the advantages of mail surveys are discussed. Low response rates form the major disadvantage of the technique and advantages of prenotification which can help to increase response rates are discussed. A limited number of studies exist on the effect of prenotification and its associated costs and benefits. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
4
1
Order By: Relevance
“…This result might be related to a finding by Mitchell and Nugent (1991), which concluded that personal prenotification did increase response rates only insignificantly compared to impersonal prenotification. Hence, we would suggest that the underlying theoretical model appears to find support, albeit its absolute effectiveness might be challenged in a DCS.…”
Section: Analysis and Resultscontrasting
confidence: 49%
“…This result might be related to a finding by Mitchell and Nugent (1991), which concluded that personal prenotification did increase response rates only insignificantly compared to impersonal prenotification. Hence, we would suggest that the underlying theoretical model appears to find support, albeit its absolute effectiveness might be challenged in a DCS.…”
Section: Analysis and Resultscontrasting
confidence: 49%
“…Using a letter to pre-notify has, generally, been more costly than no prenotification (Albaum & Strandskov, 1989), but has been cost effective compared to a commitment card (Duhan & Wilson, 1990). The use of telephone pre-notification has not been found to be cost effective compared to a no pre-notification control (Mitchell & Nugent, 1991).…”
Section: Attention-seekingmentioning
confidence: 99%
“…Response cost-effectiveness: Response cost-effectiveness equals "total survey costs" divided by the number of usable responses. "Total survey costs" refers to tangible survey costs such as postage and printing costs, and excludes less tangible costs such as time and manpower (Duhan and Wilson 1990;Mitchell and Nugent 1991).…”
Section: Delineation Of Relevant Metricsmentioning
confidence: 99%